ANALISIS INTEGRASI PASAR PISANG KEPOK - Husinsyah Husinsyah; Syahdi Rasyid (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2016)
Research aims to understand the banana kepok integration .Study was conducted since january until june 2015 .The sample done by means of 1 ) method of random simple to farmers , and 2 ) method snowballs to traders. Analysis of data using analysis integration market .The results of the study obtained a correlation coefficient integration a market is 0,924 which indicates that price to the farmers related so closely as to price to the consumer, and markets what happens is market competition imperfect.